Distinct human circulating NKp30+FcεRIγ+CD8+ T cell population exhibiting high natural killer-like antitumor potential - Correia, Margareta; Stojanovic, Ana; Bauer, Katharina; Juraeva, Dilafruz; Tykocinski, Lars-Oliver; Lorenz, Hanns-Martin; Brors, Benedikt; Cerwenka, Adelheid (Proceedings of the National Academy of Sciences of the United States of America, 2018)
CD8+ T cells are considered prototypical cells of adaptive immunity. Here, we uncovered a distinct CD8+ T cell population expressing the activating natural killer (NK) receptor NKp30 in the peripheral blood of healthy individuals. We revealed that IL-15 could de novo induce NKp30 expression in a population of CD8+ T cells and drive their differentiation toward a broad innate transcriptional landscape. The adaptor FcεRIγ was concomitantly induced and was shown to be crucial to enable NKp30 cell-surface expression and function in CD8+ T cells. FcεRIγ de novo expression required promoter demethylation and was accompanied by acquisition of the signaling molecule Syk and the “innate” transcription factor PLZF. IL-15-induced NKp30+CD8+ T cells exhibited high NK-like antitumor activity in vitro and were able to synergize with T cell receptor signaling. Importantly, this population potently controlled tumor growth in a preclinical xenograft mouse model. Our study, while blurring the borders between innate and adaptive immunity, reveals a unique NKp30+FcεRIγ+CD8+ T cell population with high antitumor therapeutic potential.